Edukasi Kesehatan dengan Triple Breast Self-Examination (BSE) Method pada Kader Kesehatan dalam Melakukan Skrining Kanker Payudara di Puskesmas Tamalanrea Jaya Kota Makassar - Gaffar, Indra; Erika, Kadek Ayu; Sabriyati, Wa Ode Nur Isnah; Hasbiah, Nurhikmawaty; Hamisah, Hamisah; Wahyuni, Andi; Yodang, Yodang; Abdullah, Lilian Arifka Juli; Jurana, Jurana; Nas, Afifah; Bakhtiar, Hasmiranda; Rahmatullah, Marhamah Putri (Universitas Baiturrahim, 2024)
Breast cancer is the most common cancer found in women. Cancer is a non-communicable disease in which there is very rapid, uncontrolled growth and development of cells and tissues. Breast self-examination (BSE) is an effective method for screening and early detection of breast cancer. BSE can be done by everyone, making it easier to detect cancer. The purpose of this community service activity is to increase knowledge and skills to health cadres related to early detection of breast cancer using the Triple Breast Self-Examination (BSE) method. The educational methods used were counseling, demonstration and discussion. A total of 40 health cadres at Tamalanrea Jaya Health Center participated voluntarily. It is hoped that from this activity health cadres will be able to better recognize and understand the breast cancer early detection method, namely Triple Breast Self-Examination (BSE).